1899 Annotated Statutes of the Indian Territory, at 243-244, ch. 19, pt. 53, § 1250 - (:unkn) unknown (My University, 1899)
Any person who shall wear or carry in any manner whatever as a weapon any dirk or bowie knife, or a sword, or a spear in a cane, brass or metal knucks, razor, or any pistol of any kind whatever, except such pistols as are used in the army or navy of the United States, shall be guilty of a misdemeanor.
Keywords: CARRY